Strongyloides spp Distribution on Orangutans in Tanjung Putting National Park, Care Center in Pangkalanbun, and Sebangau National Park - Nurcahyo, Wisnu; Prastowo, Joko (Jurnal Veteriner; Vol 14 No 2 (2013), 2013)
Strongyloides spp is a parasitic nematode in livestock, primate and human which is  considered asa danger zoonotic disease. Therefore, study about parasite distribution is very important in order to find outgenetic diversity among orangutan in quarantine, zoo and nature, as an effort to explore infection patternand life cycle of Strongyloides spp on orangutan. Amount of 326 orangutan feces were taken from threedifferent habitat of orangutan in Central Borneo, Tanjung Puting National Park, Orangutan Care Centerand Sebangau National Park. Samples which were collected from Tanjung Puting, Care Center and Sebangauwere 75, 80 and 171 respectively. Those samples were transported to the Parasitology laboratory in Facultyof Veterinary Medicine, Gadjah Mada University, Yogyakarta for examination and detection.  Prevalence ofstrongyloides in Tanjung Putting, Sebangau and Orangutan Care Center were 24%, 14,6% and 13,3%respectively. Among positive samples of Strongyloides, 62,5% were from male orangutans, while 37,5% werefrom female orangutans. Strongyloides in pre adult and baby orangutan were 91,6% and 4,2% respectively.Meanwhile, Strongyloides in adult orangutan were very rare. Orangutan habitat in Sebangau National Parkis an ideal habitat for orangutan, supported by the watery condition of peat land, so that Strongyloides re-infection become difficult. Some factors may have important role in Strongyloidoses, such as behavior,physical condition, nutrition, age, body weight, sex, immunity and social status of orangutan.
Keywords: Central Kalimantan, Strongyloidosis, orangutans